2021
DOI: 10.18632/aging.202860
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive evaluation of the efficacy and safety of LPV/r drugs in the treatment of SARS and MERS to provide potential treatment options for COVID-19

Abstract: Coronavirus disease 2019 (COVID-19) experienced an outbreak that expanded worldwide. Lopinavir/ritonavir (LPV/r), which is used effectively for severe acute respiratory syndrome (SARS) and Middle East respiratory syndrome (MERS) coronavirus infections, was applied for COVID-19 treatment given similarities in the molecular structures of these viruses. We performed a systematic review and meta-analysis to evaluate the efficacy and safety of lopinavir/ritonavir antiviral treatment in patients with SARS, MERS, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
37
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 63 publications
(37 citation statements)
references
References 33 publications
0
37
0
Order By: Relevance
“…In this study, it was shown that calcitriol can reduce the expression of the key gene FCGR3A. Previous studies (30)(31)(32) have shown that calcitriol can reduce the expression level of RAGE in cardiomyocytes, reduce the accumulation of AGE in the aortic wall of diabetic rats, reduce the expression level of AGE-induced interleukin 6 (IL-6), and inhibit the activity of NF-κB.…”
Section: Discussionmentioning
confidence: 69%
“…In this study, it was shown that calcitriol can reduce the expression of the key gene FCGR3A. Previous studies (30)(31)(32) have shown that calcitriol can reduce the expression level of RAGE in cardiomyocytes, reduce the accumulation of AGE in the aortic wall of diabetic rats, reduce the expression level of AGE-induced interleukin 6 (IL-6), and inhibit the activity of NF-κB.…”
Section: Discussionmentioning
confidence: 69%
“…Tumor stem cells can induce the production of more immunosuppressive M2 macrophages, and tumor stem cells can directly impair the activity of cytotoxic T cells to suppress the immune response [17]. In addition, cancer stem cells also play an important role in the development of cancer vaccines [18][19][20]. Therefore, tumor stem cells may be used as predictors of the therapeutic efficacy of immune checkpoint inhibition.…”
Section: Discussionmentioning
confidence: 99%
“…expression. Transfection of CX43 into human glioma cells, U251 and T98G, significantly inhibits cell proliferation, suggesting that CX43 may be a tumor suppressor gene (20).…”
Section: What Is the Implication And What Should Change Now?mentioning
confidence: 99%